2015
DOI: 10.1101/cshperspect.a020396
|View full text |Cite
|
Sign up to set email alerts
|

The Astrocyte: Powerhouse and Recycling Center

Abstract: Brain metabolism is characterized by fuel monodependence, high-energy expenditure, autonomy from the rest of body, local recycling, and marked division of labor between cell types. Although neurons spend most of the brain's energy on signaling, astrocytes bear the brunt of the metabolic load, controlling the composition of the interstitial fluid, supplying neurons with energy substrates and precursors for biosynthesis, and recycling neurotransmitters, oxidized scavengers, and other waste products. Outstanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 138 publications
3
128
1
2
Order By: Relevance
“…We therefore reasoned that ALS specific determinants within the CNS—as opposed to more general mechanisms occurring throughout the body—were responsible for the upregulation of P-gp. Astrocytes have an important role in the viability and function of CNS by secreting a number of soluble factors that could influence nearby cells (Weber and Barros, 2015). With regards to ALS, previous studies showed astrocytes as clinically determinant contributors to ALS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore reasoned that ALS specific determinants within the CNS—as opposed to more general mechanisms occurring throughout the body—were responsible for the upregulation of P-gp. Astrocytes have an important role in the viability and function of CNS by secreting a number of soluble factors that could influence nearby cells (Weber and Barros, 2015). With regards to ALS, previous studies showed astrocytes as clinically determinant contributors to ALS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The human brain, which represents ~2% of body weight, consumes a disproportionate amount of the body’s basal energy budget (roughly 20%) (for discussions, see Harris et al, 2012; Hertz et al, 2007; Stobart and Anderson, 2013; Weber and Barros, 2015). Unlike other biological systems that can use fats, amino acids, or carbohydrates/glucose for fuel, the brain is essentially dependent upon glucose for fuel (Stanley et al, 2014; Weber and Barros, 2015).…”
Section: Glutamate Transport and The Neurovascular Responsementioning
confidence: 99%
“…Unlike other biological systems that can use fats, amino acids, or carbohydrates/glucose for fuel, the brain is essentially dependent upon glucose for fuel (Stanley et al, 2014; Weber and Barros, 2015). While glycogen and glutamate provide local reserves for generation of ATP (see discussions above), neuronal activity relatively rapidly (within ~1 sec) results in an increase blood flow and delivery of glucose to the brain.…”
Section: Glutamate Transport and The Neurovascular Responsementioning
confidence: 99%
“…Brain energy metabolism is strongly dependent on glucose and major catabolic pathways were proposed to be largely subdivided in between astrocytes and neurons, the former predominantly performing glycolysis and the latter oxidative phosphorylation [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%